Associations with oral health indices for obesity risk among Japanese men and women: results from the baseline data of a cohort study - Hiroko Tanaka; Mirei Nakano; Kiyonori Kuriki; Shizuoka-Sakurag (BMC, 2022)
Abstract Background Oral health is composed of various oral health indices (OHIs), such as oral self-care habits, oral hygiene, oral function, and mastication ability. Oral self-care habits have frequently been examined for obesity risk. This study aimed to comprehensively clarify the association between OHIs and obesity risk. Methods We collected data for 15 questions on the four OHIs and measured the body mass index of 3494 men and 2552 women aged 35-79 years. Obesity was defined as a body mass index ≥25 kg/m2. The four OHIs were scored by the corresponding questions (good as "reference"), and the summed score was defined as "comprehensive OHI", that is, the fifth OHI. Each lowest tertile score was used as "reference". Using multiple logistic regression analysis, odds ratios (ORs), 95% confidence intervals (CIs), and p-values for trends were estimated. Results In the men and women, the ORs were 1.37 (1.11-1.67, < 0.01) and 2.48 (1.80-3.42, < 0.01) for oral self-care habits, and 1.78 (1.42-2.24, < 0.01) and 3.06 (2.12-4.43, < 0.01) for tooth brushing frequency, respectively. Moreover, in men, a significant trend was found for "harder rinsing out your mouth", related to "oral function". In women, the ORs were 1.74 (1.28-2.36, < 0.01) and 1.43 (1.00-2.06, < 0.01) for "comprehensive OHI" and "longer meal time" related to "mastication ability", respectively. Conclusions Our findings showed that obesity risk was associated with poor of oral health, which were comprehensively composed of various OHIs, among middle-aged and older Japanese men and women.